Passive Hybrid Storage Systems: Influence of circuit and system design on performance and lifetime. (November 2018) - Grün, Thorsten; Smith, Anna; Ehrenberg, Helmut; Doppelbauer, Martin
Abstract: Depending on the nature of a particular energy storage technology, an equivalent storage system will lead to a characteristic performance. In an extreme case the system will either provide high power (if based on capacitors) or high energy (if based on lithium ion batteries). On the other hand it will lack in energy or power, respectively. Therefore, a passive parallel connection of unlike energy storage technologies is very attractive to improve cycle life as well as power and energy density in comparison to single energy storage technologies. In this approach, different lithium ion technologies are connected with different supercapacitor technologies directly in parallel. Experimental and model-based investigations show, how the energy and power density characteristics of such systems differ from each other and which advantages can be achieved in comparison to commercial systems.